2007
DOI: 10.1021/jo070439a
|View full text |Cite
|
Sign up to set email alerts
|

Colorimetric Recognition of Anions Using Preorganized Tetra-Amidourea Derived Calix[4]arene Sensors

Abstract: The synthesis and the spectroscopic studies of the amidourea based calix[4]arene sensors 1 and 2 are described. The 4-nitrophenyl based sensor 1 was synthesized in two steps from the corresponding calix [4]arene tetraethyl ester and shown to give rise to color changes in the UV-vis spectra in DMSO upon recognition of pyrophosphate and fluoride. Fitting the changes in the absorption spectra using nonlinear regression analysis indicated strong binding of several anions by 1 such as acetate and hydrogen phosphate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
81
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 199 publications
(83 citation statements)
references
References 22 publications
(26 reference statements)
0
81
0
1
Order By: Relevance
“…In particular the ability of derivatives to complex anions (2,3) and cations (4,5) has been exploited for the development of sensors. Recently, interest has focused on the use of calixarene derivatives in biological systems be it as drugs, drug delivery systems, or imaging agents.…”
mentioning
confidence: 99%
“…In particular the ability of derivatives to complex anions (2,3) and cations (4,5) has been exploited for the development of sensors. Recently, interest has focused on the use of calixarene derivatives in biological systems be it as drugs, drug delivery systems, or imaging agents.…”
mentioning
confidence: 99%
“…19 The first study, reported by Zhang et al,20 described two 3-D framework constructed from tetra-psulfonatocalix [4]arenes and rare earth cations (i.e. Nd III and Eu III ).…”
Section: Introductionmentioning
confidence: 99%
“…14 Many different strategies have been developed for designing fluorescent chemosensors for Ppi including the use of charged receptors, 15,16 metal complexes, [17][18][19][20][21] or neutral receptors in particular urea or thiourea receptors. 15,[22][23][24][25][26] We have recently described a new family of symmetric bis-urea receptors which showed a remarkable affinity for Ppi and were able to act as a fluorimetric chemosensors for this anion, even at naked eye. 27 In particular we demonstrated that the presence of naphtyl groups as pendant arms of the ureas, facilitates the binding and the optical fluorimetric selectivity thanks to the uncommon interaction of an aromatic CH from the fluorophore with the Ppi guest.…”
Section: Introductionmentioning
confidence: 99%